2000
DOI: 10.1016/s0014-5793(00)01675-6
|View full text |Cite
|
Sign up to set email alerts
|

Chemical inhibitors: a tool for plant cell cycle studies

Abstract: Synchrony provides a large number of cells at defined points of the cell cycle. Highly synchronised cells are powerful and effective tools for molecular analyses and for studying the biochemical events of the cell cycle in plants. Usually, plant cell suspensions can be synchronised by chemical agents, which arrest the cell cycle by acting on the driving forces of the cell cycle engine such as cyclin-dependent kinase activity, enzymes involved in DNA synthesis or proteolysis of cell cycle regulators or by actin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
0
6

Year Published

2001
2001
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(111 citation statements)
references
References 62 publications
1
104
0
6
Order By: Relevance
“…1C). Because the 2-fold increase can be attributed to a doubling of incubation time, only the data for roscovitine represent definitive reversal of inhibition of DNA replication in accordance with previous findings for these inhibitors (29).…”
Section: Involvement Of Dna Replication In Pvalf-and Aba-mediated Actsupporting
confidence: 87%
See 1 more Smart Citation
“…1C). Because the 2-fold increase can be attributed to a doubling of incubation time, only the data for roscovitine represent definitive reversal of inhibition of DNA replication in accordance with previous findings for these inhibitors (29).…”
Section: Involvement Of Dna Replication In Pvalf-and Aba-mediated Actsupporting
confidence: 87%
“…Evidence for Replication and Its Inhibition in Leaves-Histone H4 synthesis occurs during S phase, and H4 transcripts serve as molecular markers for this stage of the cell cycle (29,30). High levels of H4 transcripts were detected in leaves treated with estradiolϩABA (Fig.…”
Section: Dna Replication Arrest Affects the Aba-mediated Activationmentioning
confidence: 96%
“…EdU incorporation also occurred in cells that were distant from the cut ( Figure 1I, yellow arrows) and that do not divide, suggesting that excision also induces endoreduplication. We also tested the necessity of DNA synthesis for cell cycle progression using aphidicolin, an inhibitor of DNA polymerase a and d that prevents nuclear DNA replication but not endoreduplication (Planchais et al, 2000;Quelo et al, 2002). If leaf cells were arrested in G2-phase, they would be able to divide once after excision in the presence of aphidicolin.…”
Section: Gametophore Leaf Cells Reenter the Cell Cycle In Late S-phasementioning
confidence: 99%
“…Consistently, the dominant-negative CDKA reduced the amount of RM09 and RM55 transcripts ( Figures 6D and 6E). As an alternative to the dominant-negative CDKA, we used the chemical roscovitine, which inhibits CDKs (Planchais et al, 1997(Planchais et al, , 2000. Roscovitine inhibited the accumulation of CYCB;1 (Figure 7A), cytokinesis ( Figure 7B), the accumulation of RM09 ( Figure 7C) and RM55 ( Figure 7D) transcripts, and tip growth ( Figure 7E).…”
Section: Cdka Regulates Protonema-specific Genes and Tip Growthmentioning
confidence: 99%
“…It was, however, difficult to monitor the change of CDK activity during the early phase of organogenesis because the dedifferentiation process is initiated in a single differentiated cell within the vascular bundle (28). To overcome this problem, we used a CDK inhibitor, roscovitine, which specifically inhibits CDK activities in animals (23,29) and kinase activities associated with yeast p13 Suc1 in maize (30,31). We confirmed that the CDK2-kinase activity of R2 immunoprecipitates was less sensitive to roscovitine than the CDK activities associated with p13 Suc1 in rice suspension cells (Fig.…”
Section: Up-regulation Of Cdk Activities At the Early Phase Of Culturmentioning
confidence: 99%